The influence of surface defects on the pinhole formation in silicide thin film - Belousov, I.V.; Grib, A.N.; Kuznetsov, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The growth of the CoSi layer was considered within the framework of the grain boundary diffusion model. The time dependences of the temperature due to the exothermic reaction of silicide formation as well as the dependences of the CoSi layer thickness were calculated for various values of the reaction activation energy. It was shown that the heat release at high reaction velocities can lead to the considerable increase of the temperature up to melting of the silicide and covering Co layers. The model of pinhole formation in cobalt silicide films was proposed on the basis of local melting in the reaction area at crystal defects of the silicon surface.